Institutions, reform policies, and productivity growth in agriculture: Evidence from former communist countries - Marian Rizov (NJAS - Wageningen Journal of Life Sciences, 2008)
There are important differences among former communist countries in performance of their agricultural sectors that are commonly attributed to variation in inherent institutions and reform policy choices. In this paper the link between institutions, reforms and (labour) productivity growth in agriculture is analysed within an augmented neo-classical growth model framework derived from a production function. For the empirical analysis panel data over the transition period (1990-2001) were used that cover 15 former communist countries, applying a GMM-IV estimator. Estimation results strongly support the view that the shift to individual land use, measuring farm restructuring, as well as the overall economic reforms, supported by democratic institutions, have positively contributed to the (labour) productivity growth in former communist countries' agriculture.
Keywords: Q18; Q15; 330; Institutions; Reform policies; agriculture; productivity; growth; transition